The role of raw powder diffraction data in peer review; past, present and future - García-Aranda, Miguel Ángel (My University, 2019)
Scientific data in our community can be classified, in broad terms, in three large categories: raw, reduced and derived data. IUCr has been very active in promoting the sharing of reduced and derived data for decades in independently-verified databases. The need for raw data sharing is clearly increasing, being nowadays technically feasible and likely cost-effective. Powder diffraction (PD) community is a subgroup of the crystallographic community dealing with several goals, mainly (1) average crystal structure determination; (2) quantitative phase analyses; (3) microstructural analyses; and (4) local structure determination and quantitative analyses of nanocrystalline materials. For PD, derived data for objectives (2) and (3) and to a large extend (4) can not be incorporated in ‘standard’ databases. Derived data are not independently validated, and therefore and in my opinion, the need for sharing raw PD data is even more compelling than that of sharing raw single crystal diffraction data. So, if raw diffraction data sharing is approaching, we have the responsibility to ensure that this action is useful. Hence, and as stated by John Helliwell in the introduction of this workshop, two conditions must be fulfilled. On the one hand, and from the computing point of view, the shared data must be findable, accessible, interoperable and reusable – i.e. comply with FAIR standards. However, this is necessary but not sufficient. On the other hand, and from the involved scientific community point of view, the shared data must have sufficient quality. They must be true facts and the ‘FACT and FAIR’ term has been coined. Incorporating raw powder diffraction data ‘check/validation’ in the peer review process, the FACT nature of the raw data could be established. Or at least, a minimum quality level could be ensured. Some ideas (and experiences) will be developed in the meeting, including the use of shared raw powder diffraction data by meticulous reviewers. .....
Keywords: Datos - Tratamiento; Raw data; Data sharing